Psychosocial Problems of Thalassemic in A Tertiary Care Centre, Indore - Sameer Inamdar; Anila Gangrade (Medsci Publications, 2016)
Introduction: Chronicity of thalassemia is a powerful source of emotional problems. During adolescence and young adulthood various complications may occur and patient under goes a period of psychological readjustment. Material and Methods: This was a cross sectional, interview based study of 30 adolescents and young adult thalassemic patients at Choithram Hospital and Research centre, Indore, MP, India. General Wellbeing Scale, Helplessness Scale and Psychological Wellbeing Scale were used to assess the psychosocial problem of thalassemic patients. Results: Thalassemia disease deteriorated the school performance of 56.66%.Seventeen percent thalassemics had low general wellbeing. Majority (70%) of diseased persons need to change their goals of life (ambitions) because of disease. Helplessness was felt by 37% and moderate psychological well being among 66.7%. No gender difference was noticed (P>0.05). Conclusion: Majority of thalassemics felt helpless and their general wellbeing and psychological wellbeing was average.